Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.2807/1560-7917.es.2021.26.34.2100184
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection and transmission in school settings during the second COVID-19 wave: a cross-sectional study, Berlin, Germany, November 2020

Abstract: Background School attendance during the COVID-19 pandemic is intensely debated. Aim In November 2020, we assessed SARS-CoV-2 infections and seroreactivity in 24 randomly selected school classes and connected households in Berlin, Germany. Methods We collected oro-nasopharyngeal swabs and blood samples, examining SARS-CoV-2 infection and IgG antibodies by RT-P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
49
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 23 publications
(30 reference statements)
7
49
2
Order By: Relevance
“…In a study from Germany that included 177 primary and 175 secondary school students, 142 staff and 625 household members, prevalence of SARS-CoV-2 infection was 2.7% among students, 1.4% among staff, and 2.3% among household members. Contact with confirmed cases outside the school was associated with infection among study participants [16]. Low attack rates within schools were also reported from a large study from North Carolina, USA, which included over 100,000 staff and students from 13 school districts [9].…”
Section: Discussionmentioning
confidence: 58%
“…In a study from Germany that included 177 primary and 175 secondary school students, 142 staff and 625 household members, prevalence of SARS-CoV-2 infection was 2.7% among students, 1.4% among staff, and 2.3% among household members. Contact with confirmed cases outside the school was associated with infection among study participants [16]. Low attack rates within schools were also reported from a large study from North Carolina, USA, which included over 100,000 staff and students from 13 school districts [9].…”
Section: Discussionmentioning
confidence: 58%
“…No secondary cases occurred among individuals in classes. 3 After SARS-CoV-2 infections declined in early 2021, they increased again in mid-February and peaked by mid-April (Figure ). In parallel, the SARS-CoV-2 B.1.1.7 variant gained predominance.…”
Section: Introductionmentioning
confidence: 99%
“…1 The occurrence of SARS-CoV-2 infection in school communities tends to be isolated and to produce few secondary cases. 2,3 Between June 2020 and March 2021, we examined 24 school classes (12 primary and 12 secondary) across Berlin, Germany, on 4 occasions. In November 2020, there were 9 (2.7%), 2 (1.4%), and 14…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a recent infection survey using molecular tests via polymerase chain reaction [ 14 , 15 ] showed that around 0.5–1% of children have a positive result. Also, earlier studies, including data from five countries [ 16 20 ], where all individuals were tested regardless of symptoms, found that transmission rates were considered low, mainly among elementary school children [ 16 20 ].…”
Section: Introductionmentioning
confidence: 99%